Hormonal contraceptive use in Norway, 2006-2020, by contraceptive type, age and county: A nationwide register-based study - Kari Furu; Ellen Barth Aares; Vidar Hjellvik; Øystein Karlstad (Norsk Forening for Epidemiologi, 2021)
Aim: Our aim was to study hormonal contraceptive use among women in Norway during 2006-2020 according to age groups and geography, including choice of contraceptive method, type of prescriber for long-acting reversible contraceptives, and prescriber's adherence to the national health authority recommendations. Material and methods: We conducted a nationwide drug utilization study including all women aged 16-49 years in Norway during 2006-2020. The Norwegian Prescription Database (NorPD) includes detailed information about all dispensed prescription medications from Norwegian pharmacies to individuals in ambulatory care, including year of dispensing, patient's year of birth and county of residence, and the prescriber's profession. Results: This study shows a slight increase in overall use of hormonal contraceptives among 16-49-year-olds during 2006-2018, increasing from 36% of the population to 40%. Combined oral contraceptives (COCs) was the most commonly used hormonal contraceptive method in all age groups. The use of COCs decreased during the period and the decline was greatest in those below 25 years. From 2016 80% of all new users of COCs received the recommended COC containing levonorgestrel. Use of estrogen-free contraceptives, long-acting reversible contraceptives (LARCs) and gestagen pills, has increased. After 2014 the use of LARCs, especially subdermal implant, increased steeply among younger women. Oslo had the lowest proportion of users of hormonal contraceptives among teenagers and young adults during the whole period, while among 30-49-yearolds Oslo was more in line with the other counties. Conclusion: Combined oral contraceptives (COC) was the most used hormonal contraceptive method in all age groups. However, the use of COCs decreased during the period, especially in those < 25 years, where a corresponding increase in the use of LARC has taken place, mainly from 2014 onwards. Four out of five women who initiated COC received the recommended COC type and the steep increase in use of estrogen-free LARCs in recent years implies that Norwegian prescribers have high compliance with the recommendations from the health authorities.